1996
DOI: 10.3109/02713689609008906
|View full text |Cite
|
Sign up to set email alerts
|

Tear meniscus measurement in the diagnosis of dry eye

Abstract: This study has shown tear meniscus assessment to be a useful alternative to existing tests for dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
173
2
10

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(196 citation statements)
references
References 33 publications
11
173
2
10
Order By: Relevance
“…Tear film volume is reported to be an important contributor to a stable tear film, 47,[56][57][58][59] and in this study the positive correlations observed between NIBUT and both TMH and PRTT strengthens this theory. Mainstone et al 58 reported a significant negative correlation between tear volume and staining, whereas others found none.…”
Section: Discussionsupporting
confidence: 71%
“…Tear film volume is reported to be an important contributor to a stable tear film, 47,[56][57][58][59] and in this study the positive correlations observed between NIBUT and both TMH and PRTT strengthens this theory. Mainstone et al 58 reported a significant negative correlation between tear volume and staining, whereas others found none.…”
Section: Discussionsupporting
confidence: 71%
“…A simple, clinical test for measuring human tear production dates back to Schirmer in 1903 [1]. As now practiced in a Schirmer tear test (STT) [2], a 0.2-mm thick paper strip (Standard Schirmer Tear Test Strip, Whatman standard filter paper # 41, Alcon Laboratories, Fort Worth, TX), 5-mm wide and 35-mm long, is folded at a notch located 5 mm from the rounded end of the strip and gently inserted into the inferior fornix (Table 1 lists pertinent properties of a standard Schirmer strip [2][3][4][5][6][7][8][9][10][11][12][13][14][15]). After 5 min of eye closure, or until the patient's tear fills the entire strip, the Schirmer strip is removed, and the wetted length beyond the notch is recorded [2].…”
Section: Introductionmentioning
confidence: 99%
“…AS-OCT has been used in various studies to evaluate tear meniscus, tear film, and tear dynamics, and also to determine the Eye correlations with conventional tests. 12,14,17,18,24,[27][28][29][30] Moreover, in several studies, the authors also reported that OCT has been good diagnostic sensitivity and specificity in the patients with non-Sjögren's aqueous tear deficiency (ADT), Sjögren's syndrome and lipid tear deficiency. 13,15,16,36 There are numerous majority of published results on measuring the tear meniscus using the conventional time domain OCT in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Tear meniscus height (TMH), tear meniscus depth (TMD) and tear meniscus cross-sectional area (TMA) measurements by using OCT are good indicators of tear meniscus. 14 Although a variety of recent studies suggest that measurement of tear mensicus by using OCT has potential for diagnosis and monitoring in different types of dry eye, there is a paucity of research on concerning with diagnostic significance of OCT in dry eye with systemic disorders. [15][16][17] A thorough search of the literature identified no studies of OCT findings in patients with acne rosacea.…”
Section: Introductionmentioning
confidence: 99%